Blood sugar control among type 2 diabetic patients who travel abroad: A cross sectional study. Issue 13 (March 2019) - Lin, I-Wen; Chang, Hao-Hsiang; Lee, Yi-Hsuan; Wu, Yi-Chun; Lu, Chia-Wen; Huang, Kuo-Chin
Abstract : Abstract: The dose adjustment of anti-diabetic drugs during traveling abroad remains an important issue for the diabetic patients. However, there are few studies exploring the changes in blood sugar in patients with type 2 diabetes mellitus (T2DM) when traveling abroad. The study aimed to investigate the hypoglycemic episodes, sugar control, and associated factors during travel among patients with T2DM. A questionnaire was administrated to T2DM patients visiting the family medicine clinic in a medical center from September 2016 to April 2017. The Chi-square test was used to examine the differences in risk factors of hypoglycemia between hypoglycemic group and non-hypoglycemic group. Multivariate logistic regression models were used to examine the risk factors for the hypoglycemia. A total of 65 males and 74 females completed the questionnaire. The mean age was 59.3 ± 12.1 year olds, the mean BMI was 28.1 ± 5.9 kg/m 2, and the mean HbA1C was 7.4 ± 1.1%. There was 8.6% of diabetic patients reporting hypoglycemic episodes during travel. The hypoglycemic episodes were significantly related to the numbers of crossing time zones after adjusting for possible confounders. Only 21.6% of subjects told physicians their travel plan whereas two third of the physicians did not provide pre-travel consultation. The hypoglycemic episodes sometimes occurred and were related to the numbers of crossing time zones in diabetic travelers. The proportion of pre-travel consultation was low in patients with T2DM. Besides, most of the physicians did not offer pre-travel education when patients mentioned their traveling plan. The willing and ability of physicians to offer the pre-travel diabetic education deserved further investigation.